ANALISIS DEBIT AIR PIPA BERCABANG 4 DAN 5 PADA PIPA TUNGGAL DENGAN SATU TITIK JUNCTION SEBAGAI ALTERNATIF PENGGUNAAN PIPA BERCABANG - Eko Sulisyanto; Kun Suharno; Sri Widodo (Wahana Ilmuwan, 2016)
Water is a basic necessary for life of all living beings in this world, especially humans. Water for human needs streamed from a high place to a lower place by utilizing a high pressure difference (head) or drained using a pump from a lower to a high place. The water flowed through pipes. But often we see the installation of pipes branching less regulated and do not pay attention to the effects that arise as a result of these subdivisions. In the market, there are branching pipe branched pipe usually only two or at most three, not yet branched pipe 4 and 5. Therefore, how it affects the flow of water with the same head?The results of this research the neighbor pipes branched 4 and 5 as an alternative pipeline branching in order to determine the flow of water in each pipe branched 4 and 5, knowing the losses that occur in the installation of pipelines and comparing the results of the study theoretically and the results in practice. The method in this results include preparation, tank, pipe installation, implementation discharge measurements, data analysis, reporting, and publication. To obtain data on discharge measurements using the volumetric method.The results of the branched pipe 4 obtained Q2 = 0.11 l/sec (36.66%), Q3 = 0.05 l/sec (16.67%), Q4 = 0.05 l/sec (16 , 67%), Q5 = 0.09 l/sec (30.00%). In the branched pipe 5 obtainedQ2 = 0.10 l/sec (32.26%), Q3 = 0.04 l/sec (12.90%), Q4 = 0.04 l/sec (12.90%), Q5 = 0.08 l/sec (25.81%), Q6 = 0.05 l/sec (16.13%). Losses that occur in the flow in the pipe inlet cover loss, loss curves, friction loss, loss of downsizing the pipe, and the pipe loss enlargement. Calculation of water discharge theoretical and practical results on the ground show the same value that is 0.3 liters/sec.